1978
DOI: 10.1073/pnas.75.3.1466
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of malignancy in human cells: malignant and transformed phenotypes are under separate genetic control.

Abstract: Human cell hybrids derived from malignant HeLa and normal fibroblast parental cells expressed man of the transformed properties of the HeLa parent but their tumor-producing capability was suppressed. Hybrids derived from HeLa/HeLa fusions retained both their transformed and malignant henotypes. Thus, an apparent separation of the control of the transformed versus malignant phenotype is indicated. Furthermore, several transformed properties-including lack of density-dependent inhibition of growth, lectin agglut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
40
0

Year Published

1979
1979
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(43 citation statements)
references
References 33 publications
3
40
0
Order By: Relevance
“…The observation that growth of the SW480.7-chromosome 5 hybrids is not inhibited by TGF-1l indicates that responsiveness to TGF-pl is not necessary for cells to revert to a nontumorigenic state. It should also be noted that these experiments again prove that the anchorage-independent phenotype is not universally correlated with tumorigenic behavior of human cells, a finding reported elsewhere (43)(44)(45) (34,52). Certainly, by rendering SW480.7 more responsive to the growth-inhibitory effects of TGF-1l, the introduction of chromosome 18 has resulted in cells which are more similar to colorectal adenomatous cell lines, which is very interesting, considering that the loss of TGF-1I responsiveness, like alterations of chromosome 18, is an event associated with the later stages of colorectal tumor progression.…”
Section: Resultsmentioning
confidence: 52%
See 1 more Smart Citation
“…The observation that growth of the SW480.7-chromosome 5 hybrids is not inhibited by TGF-1l indicates that responsiveness to TGF-pl is not necessary for cells to revert to a nontumorigenic state. It should also be noted that these experiments again prove that the anchorage-independent phenotype is not universally correlated with tumorigenic behavior of human cells, a finding reported elsewhere (43)(44)(45) (34,52). Certainly, by rendering SW480.7 more responsive to the growth-inhibitory effects of TGF-1l, the introduction of chromosome 18 has resulted in cells which are more similar to colorectal adenomatous cell lines, which is very interesting, considering that the loss of TGF-1I responsiveness, like alterations of chromosome 18, is an event associated with the later stages of colorectal tumor progression.…”
Section: Resultsmentioning
confidence: 52%
“…All chromosome 18-SW480.7 hybrids had RNA levels similar to that shown in lanes 1 to 3. (39,44,45). The observation that growth of the SW480.7-chromosome 5 hybrids is not inhibited by TGF-1l indicates that responsiveness to TGF-pl is not necessary for cells to revert to a nontumorigenic state.…”
Section: Resultsmentioning
confidence: 75%
“…In addition, the tumorigenic parental cell line D98-AH2 was studied. The parental non-tumorigenic fibrobast used in the original cell fusion (Stanbridge et al, 1982) was difficult to obtain so a non-tumorigenic foetal fibroblast cell line of similar type (MRC-5) was also included in the study. The tumorigenic status of these cells was reported by Stanbridge et al (1982) and has been confirmed in this laboratory (Gowing et al, 1984 …”
Section: Measurement Of [Ca2 ]mentioning
confidence: 99%
“…In this system, tumorigenicity of the cell lines is defined by the ability of the hybrids to grow progressively in nude mice and not by in vitro characteristics associated with transformed cells; like anchorage independent growth, lectin agglutination and dependence on serum growth factors (Stanbridge et al, 1982). One of the few in vitro characteristics which does correlate with tumorigenicity in these cells is the disruption of the microfilaments (Gowing et al, 1984), a complex process which may be influenced by the activity of calcium-dependent regulatory proteins.…”
mentioning
confidence: 99%
See 1 more Smart Citation